Short implants (≤6 mm) versus longer implants with sinus floor elevation in atrophic posterior maxilla: a systematic review and meta-analysis - Fang Hua; Qi Yan; Meiying Su; Bin Shi (BMJ Open)
Objectives To compare the use of short implants (≤6 mm) in atrophic posterior maxilla versus longer implants (≥10 mm) with sinus floor elevation.Design A systematic review and meta-analysis based on randomised controlled trials (RCTs).Data sources Electronic searches were conducted in PubMed, Embase and the Cochrane CENTRAL. Retrospective and prospective hand searches were also performed.Eligibility criteria RCTs comparing short implants (≤6 mm) and longer implants (≥10 mm) with sinus floor elevation were included. Outcome measures included implant survival (primary outcome), marginal bone loss (MBL), complications and patient satisfaction.Data extraction and synthesis Risks of bias in and across studies were evaluated. Meta-analysis, subgroup analysis and sensitivity analysis were undertaken. Quality of evidence was assessed according to Grading of Recommendations Assessment, Development and Evaluation.Results A total of seven RCTs involving 310 participants were included. No significant difference in survival rate was found for 1–3 years follow-up (RR 1.01, 95% CI 0.97 to 1.04, p=0.74, I²=0%, moderate-quality evidence) or for 3 years or longer follow-up (RR 1.00, 95% CI 0.97 to 1.04, p=0.79, I²=0%, moderate-quality evidence). However, short implants (≤6 mm) showed significantly less MBL in 1–3 years follow-up (MD=−0.13 mm, 95% CI −0.21 to 0.05; p=0.001, I²=87%, low-quality evidence) and in 3 years or longer follow-up (MD=−0.25 mm, 95% CI −0.40 to 0.10; p=0.001, I²=0%, moderate-quality evidence). In addition, short implant (≤6 mm) resulted in fewer postsurgery reaction (RR 0.11, 95% CI 0.14 to 0.31, p<0.001, I²=40%, moderate-quality evidence) and sinus perforation or infection (RR 0.11, 95% CI 0.02 to 0.63, p=0.01, I²=0%, moderate-quality evidence).Conclusions For atrophic posterior maxilla, short implants (≤6 mm) are a promising alternative to sinus floor elevation, with comparable survival rate, less MBL and postsurgery reactions. Additional high-quality studies are needed to evaluate the long-term effectiveness of short implants (≤6 mm).Trial registeration number The protocol has been registered at PROSPERO (CRD42018103531).